THE DEVELOPMENT OF HIGH-TECH BUSINESS IN UKRAINE - Marharyta Chepeliuk; Kateryna Kutsenko (Izdevnieciba "Baltija Publishing", 2021)
Both technology and business are changing in the world. The new paradigm of the world is emerging in the form of systems, affecting all aspects of the activities of society and market players. The scale and complexity of transformation will be different from what humanity has experienced before. It is not yet possible to predict with great precision how it will unfold, but one thing is clear: the answer must be integrated and comprehensive, from the public and private sectors in scientific community, business and society. In the new economic environment, economic agents have to go through the processes of digital transformation that are necessary to improve. The purpose of the article is to define the main directions of the development of digitalization and to analyse Ukraine's place in the world by the level of development of digitalization. Methodical tools of the study were methods of analysis and synthesis, deduction and induction, search for causal relationships. The article presents the results of empirical analysis of the main trends in the Ukrainian market during the pandemic and their relationship with the processes of digitalization. The article analyzes the development trends and the size of the digital economy in Ukraine and in other countries of the world. Key numerical trends have been identified that will determine the direction of this type of economy. It has been proved that digitalization must be carried out in accordance with the principles of equal access, benefit creation, economic growth, the promotion of the information society and the orientation towards cooperation. The advantages of the digitalization of Ukrainian economy are presented, as well as the threats and risks that will arise from this process are indicated.